Serotonin circuits act cooperatively with pathophysiology of opioid use disorder - Arakawa Hiroyuki; Ozawa Akihiko (Addiction Neuroscience)
Opioid abuse and its negative effect have become a critical epidemic, putting our health and society in jeopardy. Opioids are effective treatment for pain, but at risk for developing associated health threatening impacts including the euphoria associated relapsing effects, persistent occurrence with addictive and withdrawal symptoms, and consequent respiratory depression and apnea. The opioid use disorder (OUD), represented as those recurring phases of symptoms, is initiated with mediation of opioid receptor signaling pathway and subsequent neurocircuitry transformation with homeostatic and motivational change. It has been imperative to establish modulatory mechanisms and alternative treatments to mitigate OUD. This review deals with central serotonin (5-HT) system as a cooperative mediator with OUD-related neural processing. We briefly introduce molecular base of opioid receptors and available research tools in mouse models and examine OUD-phase dependent circuit mechanisms, including pain, addiction, and respiratory depression. We interrogate the potential neural roles of 5-HT in OUD-related symptoms including 5-HT toxicity and pathophysiology and discuss potential availability of 5-HT-related agents as a neuromodulatory therapeutic interacting with opioid mediated neural mechanisms and the OUD-related symptoms.